Perancangan Sistem Informasi Akuntansi Persediaan Barang Habis Pakai Menggunakan Microsoft Visual Studio 2010 di Dinas Pendidikan Kota Bandung - Agustiningsih, Elli (POLITEKNIK NEGERI JAKARTA, 2021)
Inventory is one of the means which government agencies, especially inthe Bandung City Education Office, can support their activities. However, the management process is still based on Microsoft Excel, which is considered less effective due to frequent errors in recording, resulting in an inventory stock inaccurate, and the time it takes to produce reports. This researchhas the aim of solving the problems faced by the Bandung City Education Office in managing inventory. An inventory information system application is being designed which is expected to make it easier for staff officers to manage incoming goods, outgoing goods, and calculateinventory stock using the FIFO (first in first out) method. It is effective and efficient and produces accurate and accountable inventory reports. The application design is made in Microsoft Visual Studio 2010, the application development method is waterfall, DFD(Data Flow Diagram)and the testingmethod is black box. Application inventory information system can be directly applied to inventory managementat the Bandung City Education Office. Author refers to uses data from observations and interviews in the field while designing this application.